Dentin dysplasia: diagnostic challenges. (11th June 2018) - Alhilou, Ahmed; Beddis, Hannah P; Mighell, Alan J; Durey, Kathryn
Abstract : Dentin dysplasia(DD) is a rare autosomal dominant disorder associated with disturbance of the dentin. While the crowns appear clinically normal, on radiography, the pulp spaces appear partially or completely obliterated, with short blunted roots, and multiple periapical radiolucencies affecting the apparently sound teeth. Clinical signs include spontaneous abscess formation or increased tooth mobility which can lead to exfoliation. DD can therefore have a significant impact on the patient's dentition, and treatment is often challenging. Shields' classification of dentin disorders has been recently criticised for failing to consider differential variations and expressions of these disorders. This paper describes a case of a 23-year-old woman with previously undiagnosed DD, who presented with clinical and histological features belonging to several of these diseases, thus highlighting the potential diagnostic challenges faced with Shields' classification.